2008
DOI: 10.1194/jlr.m700254-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The LXR agonist T0901317 promotes the reverse cholesterol transport from macrophages by increasing plasma efflux potential

Abstract: The liver X receptors (LXRs) have been shown to affect lipoprotein plasma profile, lipid metabolism, and reverse cholesterol transport (RCT). In the present study, we investigated whether a short-term administration of the synthetic LXR agonist T0901317 (T0) to mice may affect RCT by modulating the capacity of plasma to promote cellular lipid efflux. Consistent with previous data, the pharmacological treatment of mice caused a significant increase of macrophage-derived [ 3 H]cholesterol content in plasma, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 32 publications
5
56
0
1
Order By: Relevance
“…On the other hand, the treatment of high dose TO901317 (10 μmol/L) could increase the extracellular cholesterol accumulation. It was predicted that the LXR activation increases the cholesterol efflux from the hepatocytes, and a similar result reported by Zanotti et al, showed that in vivo stimulation of LXR by TO901317 increase the efflux of cholesterol from peritoneal macrophages (Zanotti et al, 2008). Another previous study showed that LXR agonist TO901317 has been shown to induce the expression of ABCA1 and other LXR-responsive genes.…”
Section: General Remarkssupporting
confidence: 62%
“…On the other hand, the treatment of high dose TO901317 (10 μmol/L) could increase the extracellular cholesterol accumulation. It was predicted that the LXR activation increases the cholesterol efflux from the hepatocytes, and a similar result reported by Zanotti et al, showed that in vivo stimulation of LXR by TO901317 increase the efflux of cholesterol from peritoneal macrophages (Zanotti et al, 2008). Another previous study showed that LXR agonist TO901317 has been shown to induce the expression of ABCA1 and other LXR-responsive genes.…”
Section: General Remarkssupporting
confidence: 62%
“…Feces samples were collected at 24 and 48 hours after the injection of radiolabeled cells and extracted by the method of Bligh and Dyer. 13,22 […”
Section: Macrophage Rct In Vivomentioning
confidence: 99%
“…Plasma was isolated by low-speed centrifugation and stored at Ϫ80°C until use. Livers were extracted using the method of Bligh and Dyer 13,22 and counted by liquid scintillation addition. Feces samples were collected at 24 and 48 hours after the injection of radiolabeled cells and extracted by the method of Bligh and Dyer.…”
Section: Macrophage Rct In Vivomentioning
confidence: 99%
See 2 more Smart Citations